IEEE-EMBS International Conference on Biomedical and Health Informatics (BHI) 2014
DOI: 10.1109/bhi.2014.6864433
|View full text |Cite
|
Sign up to set email alerts
|

A method for modeling surrounding tissue support and its global effects on arterial hemodynamics

Abstract: We propose a methodology for separating the total stiffness of arteries, determined in vivo, into stiffness of the arterial wall and stiffness of the surrounding tissue. An effective perivascular pressure is considered which introduces a radial constraint. Next, based on vivo data, acquired at diastolic pressure, the cross-sectional area at zero pressure is estimated. Finally, the stiffness of the arterial wall and of the surrounding tissue are determined based on a model with two parallel springs. By employin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…First of all, all 15 patient datasets of this cohort had aortic valve disease, which leads to a modification of the flow jet through the aortic valve and potentially to an adaptation of the wall properties (especially in the ascending aorta and in the aortic arch). Secondly, previous research has shown that the surrounding tissue of the aorta has a considerable effect on the haemodynamics, leading to higher wave speed, and lower total compliance [33]. Since the various structures surrounding the aorta have different elastic properties, they provide spatially varying external tissue support along the centreline of the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, all 15 patient datasets of this cohort had aortic valve disease, which leads to a modification of the flow jet through the aortic valve and potentially to an adaptation of the wall properties (especially in the ascending aorta and in the aortic arch). Secondly, previous research has shown that the surrounding tissue of the aorta has a considerable effect on the haemodynamics, leading to higher wave speed, and lower total compliance [33]. Since the various structures surrounding the aorta have different elastic properties, they provide spatially varying external tissue support along the centreline of the aorta.…”
Section: Discussionmentioning
confidence: 99%